ANALISIS PROSES PENGUNGKAPAN DIRI MELALUI KONTEN "BERBAGI PERSPEKTIF" PADA YOUTUBE MENJADI MANUSIA - Farahdina Hanafitri Azzahra (2021)
Nowadays, interpersonal communication is closely related to technological developments. The self-disclosure process which is generally a face to face communication, can be done virtually through media social. Self-disclosure on social media can be seen through the content "Berbagi Perspektif" on Menjadi Manusia's YouTube account. The use of YouTube allows process of self-disclosure become public consumption because it can be seen by the wider community The purpose of this research is to analyze the self-disclosure process of guest stars in the "Berbagi Perspektif" content, which is the interpersonal communication mediated by computers. This research focus on concepts and theories related to self-disclosure and computer mediated communication theory (CMC). The method used is descriptive qualitative by analyzing five videos from "Berbagi Perspektif" content that has been uploaded. There are seven stages of self-disclosure through the content of "Berbagi Perspektif" which have several differences when associated with the Depth Level of Communication. Self-disclosure through the content of "Berbagi Perspektif" is more to the point than the conventional self-dislocure it self. Positive valence was found in the form of gues stars's present and better condition, positive behavioral expressions, expectations, and positive feelings. Negative valence is seen in expressions related to things in the past such as unpleasant or even detrimental traits, unpleasant experiences and behaviors of oneself or others, difficulties experienced, and the way guest stars judge themselves by negative way. This study also found the factor of guest stars expressing themselves through the content of "Berbagi Perspektif", there are Self-Expression and Competence Factors.